Aqueous phase leachates from pure and commercial microplastics differentially affect the physiology and metabolism of Chlorella sp. MM3 - Sudharsanam Abinandan; Nadeeka Lakmini Obadamudalige; Tapati Roy; Kadiyala Venkateswarlu; Geoff R. MacFarlane; Mallavarapu Megharaj (Environmental Pollution, 2026)

What feathers reveal about metal concentrations in bird tissues: An analysis of the global literature - Mattea J. Taylor; Md Rushna Alam; Andrea S. Griffin; Allison C. Luengen; Geoff R. MacFarlane (Journal of Hazardous Materials, 2026)

Spatial Distribution and AirQ + -Based Health Risk Analysis of Particulate Matter in Bangladesh’s Industrial Hubs - Md. Kamrul Hossain; Rubaiatul Islam Zerin; Humaira Rashid; Umma Suraiya Parvin Kakon; Mst. Sadia Siddika Trina; Laila Anjum Eva; Shahin Ali; Mohammad Omar Faruk Molla; Md. Saikoth Jahan; Md. Assraf Seddiky; Sazal Kumar; Mohd. Maniruzzaman; et al. (Water, Air, & Soil Pollution, 2026)
Rapid urbanisation and population growth in Bangladesh have intensified ambient particulate matter (PM 2.5 and PM 10 ) pollution, posing critical threats to public health. This study assessed PM concentration in three major industrial cities, Dhaka, Narayanganj, and Gazipur. PM concentrations were measured using an Air Particle Counter and an optimised air-quality sensor. PM measurements were conducted at 138 sampling points across Dhaka, Narayanganj, and Gazipur in October 2023, a climatologically stable late-autumn period, providing a reliable baseline for assessing ambient PM levels. Long-term chronic and acute diseases were quantified using the WHO AirQ + tool, including acute lower respiratory infection (ALRI) in children, chronic obstructive pulmonary disease (COPD), ischemic heart disease (IHD), stroke, and lung cancer (LC) in adults. The study revealed that the average PM 2.5 concentrations of 74.04, 56.70, and 63.99 µg/m 3 exceeded WHO standards in three cities and exceeded BD standards only in Dhaka, while PM 10 levels exceeded only WHO standards. A strong correlation was observed between PM 2.5 and PM 10 . Meteorological analysis indicated that wind speed and direction were key dispersion drivers, whereas temperature and humidity showed weak inverse exponential relationships with PM levels. Hazard Quotient (HQ) derivation revealed significant non-cancer health risks, with values exceeding unity. In contrast, PM 2.5 significantly affected ALRI mortality among children, with rates of 0.52, 0.44, and 0.49 per 100,000 in Dhaka, Narayanganj, and Gazipur, respectively. In adults, stroke was the leading PM 2.5 -related cause of death, with rates of 9.87, 9.13, and 9.63 per 100,000 in these cities. IHD deaths were also high, while LC and COPD mortality ranged from low to moderate. The study underscores the substantial public health implications of persistent PM pollution across Bangladesh’s industrial cities and reinforces the urgency of implementing coherent regulatory interventions. To strengthen the precision of exposure assessments and support more robust evidence-based policymaking, future investigations should incorporate multi-seasonal sampling, extended temporal monitoring, and broader spatial representation across diverse industrial zones.

Assessment of legacy and emerging contaminants in sediment of an Australian deepwater ocean outfall - Sazal Kumar; Megan Andrew-Priestley; Hsuan-Cheng Lu; Frederic D.L. Leusch; Allison C. Luengen; Zoe Rogers; Katie Newton; Geoff R. MacFarlane (Marine Pollution Bulletin, 2026)

Exposure to lead (Pb) alters the outcomes of female-female competition for resources in the semaphore crab, Heloecius cordiformis - Rosemary Patrick; Louise Ardouin; Andrea S. Griffin; Allison C. Luengen; Mohammad Mahmudur Rahman; Kim Colyvas; Wayne O’Connor; Geoff R. MacFarlane (Aquatic Toxicology, 2026)

Lipidomic alterations in oysters caused by environmentally relevant exposure to microplastics and estrogenic endocrine disrupting chemicals - Sazal Kumar; Wayne O’Connor; Steven D. Melvin; Frederic D.L. Leusch; Allison C. Luengen; Rafiquel Islam; Chenglong Ji; Junfei Zhan; Geoff R. MacFarlane (Ecotoxicology, 2026)
There is a ubiquitous co-occurrence of microplastics (MPs) and estrogenic endocrine disrupting chemicals (EEDCs) in aquatic environments. Their combined presence may induce sub-lethal stress in aquatic organisms, like molluscs, which may adapt to the stress through adjusting the lipidome. This study explored the individual and combined effects of polyethylene microplastics (PE-MPs) and a mixture of EEDCs at environmentally realistic concentrations on the lipidome of the Sydney rock oyster ( Saccostrea glomerata ). After seven days exposure, lipids were measured in the digestive glands and gonads using proton nuclear magnetic resonance ( 1 H NMR) spectroscopy. Permutational analysis of variance (PERMANOVA) revealed the lipidome of oysters exhibited treatment differences with interactions between sex and tissue type. Subsequent post-hoc analysis revealed the male digestive gland to be significantly more responsive than the other tissues tested. An increase in cholesterols and aldehydes in all treatments compared to controls was ascribed to an adaptive response to transient oxidative stress in oysters, which was alleviated by increased food intake. There was a significantly greater effect of the EEDCs mixture than PE-MPs in oysters. The combined oxidative stress of PE-MPs and EEDCs from co-exposure did not exceed the individual effects of PE-MPs and EEDCs, which may relate to low exposure concentrations of PE-MPs, selective rejection of MPs in pseudofeces, or poor vector role of smooth surfaced PE-MPs.

Acute disturbance, but chronic re-equilibration of the oyster metabolome to 17β-estradiol and nonylphenol exposure - Sazal Kumar; Wayne A. O’Connor; Allison C. Luengen; Frederic D.L. Leusch; Steve D. Melvin; Chenglong Ji; Junfei Zhan; Geoff R. MacFarlane (Aquatic Toxicology, 2026)

Environmental DNA as a tool for detecting ocean outfall impacts and environmental gradients in coastal ecosystems - Jodie Gibb; Megan Huggett; Margaret Platell; Geoff MacFarlane; Richard Man Kit Yu; Craig Evans; Megan Andrew-Priestley; Michael Stat (Science of The Total Environment, 2026)

Contaminants influence the outcomes of the male-male competition component of sexual selection under field conditions - Rosemary Patrick; Andrea S. Griffin; Kim Colyvas; Allison Luengen; Mohammad Mahmudur Rahman; Chiedza Francisca Munyeza; Geoff R. MacFarlane (Environmental Pollution, 2025)

A metabolomic analysis on the toxicological effects of the universal solvent, dimethyl sulfoxide - Sazal Kumar; Rafiquel Islam; Wayne O'Connor; Steve D. Melvin; Frederic D.L. Leusch; Allison Luengen; Geoff R. MacFarlane (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Exploring the co-exposure effects of environmentally relevant microplastics and an estrogenic mixture on the metabolome of the Sydney rock oyster - Sazal Kumar; Wayne O'Connor; Rafiquel Islam; Frederic D.L. Leusch; Steve D. Melvin; Geoff R. MacFarlane (Chemosphere, 2024)

Sub-lethal effects of metal(loid) contamination on the halophyte Sarcocornia quinqueflora with links to plant photosynthetic performance and biomass – A field study - Rebecca A.L. Voigt; Geoff R. MacFarlane (Marine Pollution Bulletin, 2024)

Intergenerational toxicity of 17α-ethinylestradiol (EE2): Effects of parental exposure on early larval development and transcriptomic profiles in the Sydney rock oyster, Saccostrea glomerata - Rafiquel Islam; Richard Man Kit Yu; Wayne A. O’Connor; Xiao Lin; Keng Po Lai; Frederic D.L. Leusch; Geoff R. MacFarlane (Journal of Hazardous Materials, 2024)

Tolerance of the Australian halophyte, beaded samphire, Sarcocornia quinqueflora, to Pb and Zn under glasshouse conditions: Evaluating metal uptake and partitioning, photosynthetic performance, biomass, and growth - Rebecca A L Voigt; Geoff R MacFarlane (Aquatic Toxicology, 2024)

Upregulation of antioxidant enzymes contribute to the elevated tolerance of Juncus acutus offspring from metal contaminated environments - Md Rushna Alam; Geoff R. MacFarlane (Environmental Pollution, 2024)

Atmospheric Particulate Matter and Associated Trace Elements Pollution in Bangladesh: A Comparative Study with Global Megacities - Sazal Kumar; Narottam Saha; Anika Amir Mohana; Md. Sabbir Hasan; M. Safiur Rahman; Michele Elmes; Geoff R. MacFarlane (Water, Air, & Soil Pollution, 2024)
Air quality degradation due to high levels of atmospheric particulate matter (PM) of various size fractions and the associated potentially toxic trace elements (PTEs) is a global concern. This article provides a thorough review and analysis of the temporal and spatial distribution of PM and PTEs in Bangladesh, offering a comprehensive assessment with other megacities worldwide based on existing literature. This study provides insights into the sources and transport mechanisms of PM and their link to human health. The level of PM was consistently high in Dhaka (capital of Bangladesh), with occasional higher levels in the surrounding cities. Different functional areas within Bangladesh show varying levels of PM, with total suspended particulates (TSP) being notably prevalent. When compared to megacities worldwide, African and Asian megacities, like India, Pakistan, Nigeria, and Egypt, exhibited higher PM concentrations. The concentration of PM-associated PTEs varies significantly among megacities and PM 10 tends to have relatively higher concentrations of PTEs compared to other fractions in Bangladesh. Pb in ambient air was found across most megacities, with a temporal increase in Bangladesh. TSP exhibited the highest relative Pb content, followed by PM 10 and PM 2.5 . Temporal factors, geographic locations, meteorological conditions, and anthropogenic activities contribute to the variation in PM and associated PTEs concentration in Bangladesh and global megacities. Ultimately, this study would aid policymakers in assessing the magnitude of PM pollution in Bangladesh compared to other megacities considering regional factors.

Uptake and distribution of metal(loid)s in two rare species of saltmarsh, blackseed samphire, Tecticornia pergranulata, and narrow-leafed wilsonia, Wilsonia backhousei, in New South Wales, Australia - Rebecca A.L. Voigt; Md Rushna Alam; Taylor J. Stein; Mohammad Mahmudur Rahman; Mallavarapu Megharaj; Geoff R. MacFarlane (Marine Pollution Bulletin, 2024)

Influence of soil physicochemical properties, particle size fractions and mineralogy on the leaching potentials of arsenic and antimony in abandoned mine soils - A.S.M. Fazle BARI; Dane LAMB; Geoff R. MACFARLANE; Mohammad Mahmudur RAHMAN (Pedosphere, 2023)

eDNA metabarcoding reveals shifts in sediment eukaryote communities in a metal contaminated estuary - Alessandra L. Suzzi; Megan J. Huggett; Troy F. Gaston; Geoff R. MacFarlane; Md Rushna Alam; Jodie Gibb; Michael Stat (Marine Pollution Bulletin, 2023)

Offspring of metal contaminated saltmarsh (Juncus acutus) exhibit tolerance to the essential metal Zn but not the nonessential metal Pb - Md Rushna Alam; Mohammad Mahmudur Rahman; Richard Man Kit Yu; Geoff R. MacFarlane (Environmental Pollution, 2023)

Pollution status and ecological risk assessment of metal(loid)s in the sediments of the world's largest mangrove forest: A data synthesis in the Sundarbans - Sazal Kumar; Pritom Bhowmik Akash; Rafiquel Islam; Geoff R. MacFarlane (Marine Pollution Bulletin, 2023)

Lead (Pb) Contamination in Agricultural Products and Human Health Risk Assessment in Bangladesh - Sazal Kumar; Rafiquel Islam; Pritom Bhowmik Akash; Md Hafijur Rahaman Khan; Ram Proshad; Joyanto Karmoker; Geoff R. MacFarlane (Water, Air, & Soil Pollution, 2022)
Lead (Pb) is a widely occurring heavy metal employed in industrial products and hence released into the environment, causing several environmental health risk concerns. This study comprehensively surveyed the literature on Pb contamination in different agricultural foods and food products commonly consumed by Bangladeshi inhabitants and assessed associated cancer and non-cancer health risks. Cereals (i.e., rice, wheat and maize) contained very high concentrations of Pb among the selected food items, the highest was found in wheat (4.04 µg g −1 ), while rice and maize were 2.22 and 1.43 µg g −1 , respectively, that exceeded the maximum allowable concentration (MAC, 0.20 µg g −1 ) for cereals. Vegetables contained higher Pb than the MAC of 0.01 µg g −1 , except for mushroom, green banana, cauliflower and arum. In addition, pulses also contained a moderate amount of Pb; however, fruits contained a low level of Pb, except for mangoes. When examining spatial differences in Pb contamination, most districts exhibited high Pb content in cereals; however, vegetables of the Tangail district exhibited the highest Pb concentrations (2.17 µg g −1 ), originating from industrial operations and vehicular emissions. In terms of human health risk assessment, it was observed that consumption of rice, zucchini, tesla gourd, sponge gourd, okra, drumstick lib, chili and cabbage might pose non-cancer health risks (THQs > 1); however, fruits and pulses do not pose any non-cancer health risks to Bangladeshi residents. Most of the cereals and vegetables showed a higher value than 10 −6 , indicating a potential cancer risk; however, fruits and pulses showed lower risk only marginally exceeding the lower allowable limit (i.e., 10 −6 ). Graphical abstract

Assessment of the Effects of Sediment-Associated Metals and Metalloids on Mangrove Macroinvertebrate Assemblages - Rebecca A. L. Roe; Thi Kim Anh Tran; Maria J. Schreider; Geoff R. MacFarlane (Water, Air, & Soil Pollution, 2020)

Lethal and Sub-Lethal Effects of Aluminium on a Juvenile Penaeid Shrimp - Angela Russell; Geoff R. MacFarlane; Barbara Nowak; Natalie A. Moltschaniwskyj; Matthew D. Taylor (Thalassas: An International Journal of Marine Sciences, 2019)

Investigating responses to control: a comparison of common myna behaviour across areas of high and low trapping pressure - Marie C. Diquelou; Geoff R. MacFarlane; Andrea S. Griffin (Biological Invasions, 2018)

Effects of salinity and temperature on the germination of Phragmites australis, Juncus kraussii, and Juncus acutus: Implications for estuarine restoration initiatives - Mary E. Greenwood; Geoff R. MacFarlane (Wetlands, 2006)